GAYA BAHASA DAN NILAI PENDIDIKAN KARAKTER DALAM KUMPULAN CERPEN DILARANG MENCINTAI BUNGA-BUNGA KARYA KUNTOWIJOYO SEBAGAI MATERI AJAR DI SMP - Dimas Pramudya Nugroho; Sumarwati Sumarwati; Edy Suryanto (Universitas Sebelas Maret, 2019)
This research is a qualitative descriptive study. The sampling technique is done by using purposive sampling. Data validity using triangulation method. Data analysis techniques in this study using interactive analysis techniques: (1) data reduction; (2) data presentation; (3) drawing conclusions. The results of research: (1) The use of stylistic in an ontology of short stories Dilarang Mencintai Bunga Bunga, 12 types of dominant language stylistic are found and the most dominating is hyperbole stylistic; (2) The use of imagery in ontology of short stories Dilarang Mencintai Bunga-Bunga. it is found 4 forms of imageries and the most dominating is vision; (3) it is found 5 values of character education building in an ontology of short stories Dilarang Mencintai Bunga-Bunga namely: a) religious; b) independent; c) integrity; d) community self-help; e) nationalist; and (4) The ontology of short stories Dilarang Mencintai Bunga Bunga has the suitability criteria that can be used as teaching materials that are: a) the language is light, easy to understand; b) suitable with age, interest, and psychological development; c) suitable with the socio-cultural environment of learners; d) enhance sense of curiosity. Implementation of research results. The ontology of short stories Dilarang Mencintai Bunga Bunga as literature materials in junior high school is relevant to Core Competence and Basic Competence.